0573 Daytime and Nighttime Sleep and Symptoms of Depression and Anxiety in Adults with Inflammatory Bowel Disease. (25th May 2022) - Conley, Samantha; Proctor, Deborah; Jeon, Sangchoon; Redeker, Nancy
Abstract: Introduction: Inadequate sleep duration and daytime napping are associated with symptoms of depression and anxiety in the general population. People with autoimmune diseases frequently experience poor sleep and depressive and anxious symptoms; however, little is known about how sleep might contribute to depressive and anxious symptoms in this population. The purpose of this study was to explore the associations between nighttime sleep and naps and depressive and anxious symptoms in adults with inflammatory bowel disease (IBD). Methods: We conducted a cross-sectional feasibility study of adults with IBD (Crohn's disease and ulcerative colitis) ages 18 to 60 years recruited from a single academic IBD center. We measured depressive and anxious symptoms using the Patient-Reported Outcomes Measurement Information System (PROMIS) measures. We elicited nighttime sleep [sleep duration, efficiency, and wake after sleep onset (WASO)] using wrist-worn actigraphs (Philips Spectrum Plus) and elicited naps and perceived sleep quality (analog scale 0-100) with sleep diaries over 10 days. Results: We included 35 adults [age M = 37.8 (14.0); female N = 21 (60.0%); Crohn's disease N = 18 (51.4%); clinical remission N= 22 (63.9%)]. Mean depression (51.4 SD= 9.1) and anxiety (52.6 SD = 9.9) were over the population-based cut-offs. Additionally, nightly sleep duration was short (M = 391.9 minutes SD = 52.5). Sleep efficiency (M = 83.0% SD = 5.5) was low, and WASO (M = 41.8 minutes SD = 19.9) was high. Twenty-one (60%) participants reported taking at least one nap (median = 2, range 1-7) over the 10 days. Depressive and anxious symptoms were higher in people who napped than those who did not nap with a moderate effect size (Cohen's d = -.309, -.466 respectively). Sleep quality was correlated with symptoms of depression (r = .622, p < .001) and anxiety (r = .638, p < .001). No other sleep characteristics were associated with depressive and anxious symptoms (r < .1, p > .59). Conclusion: Health care providers should assess for the presence of depression and anxiety in people with IBD who regularly nap and report poor sleep quality. Future research regarding the treatment of sleep, depression, and anxiety is needed in this population. Support (If Any): American Nurses Foundation